The Relationship Between Mothers' Knowledge Of Nutrition And The Risk Of Stunting In Toddlers At Community Health Center X - Fadiyatul Mufidah, Imtiyaaz; Roza Indra Yeni; Ricky Riyanto Iksan; Reghula Maryeti Sandra (Jurnal Life Birth, 2025)
Background: Stunting is a condition of stunted growth in toddlers due to chronic malnutrition and other factors such as maternal knowledge, immunization, family economic status and lack of nutrition. The purpose of this study is to determine the relationship between maternal knowledge about nutrition and the risk of stunting in toddlers at Community Health Center X. Research Methods: This study uses a quantitative method with a cross-sectional approach, the population of this study were mothers who have toddlers who visited Community Health Center X, this study involved 90 respondents with a total sampling technique. Results: The results showed that the majority of mothers, 65 people (92.9%) had good knowledge. Among mothers with good knowledge, there were 9 toddlers (13.8%) stunting, and 56 toddlers (86.2%) were not stunted. The analysis showed that there was no significant relationship between maternal knowledge about nutrition and the risk of stunting in toddlers with a p-value of 1,000. Conclusion: Good maternal knowledge is not significantly related to the risk of stunting in toddlers. Therefore, it is important for nutritional interventions to not only focus on increasing knowledge, but also include a more comprehensive approach..